Obstacle Sensing Autonomous Mobile Robot - Azrihan Bin Abdullah, Azrihan (Universiti Teknologi Petronas, 2010)
The aim of this project is to design an autonomous mobile robot that have the ability to sense and avoid obstacles with considerable amount of cost. The robot is requires to have its own movement based on sensor and programmed microcontroller. The scope of the study for this project is covering several areas such as electronic circuit design, programming based software and mechanical design.